Comparative genomics and the roots of human behavior. Issue 3 (March 2023) - Cook, Jennifer L.; Robinson, Gene E.
Abstract: Advances in genomics provide tools to test whether similar behaviors in distinct species have statistically similar brain transcriptomic signatures. Here, we (a genomicist and a cognitive neuroscientist) suggest that these techniques can help cognitive scientists tackle some of the most pressing questions about the roots of human behavior.